An Atomistic Study of the Thermoelectric Signatures of CNT Peapods - Mendez, Alvaro Rodriguez; Sandonas, Leonardo Medrano; Dianat, Arezoo; Gutierrez, Rafael; Cuniberti, Gianaurelio (Giovanni) (Journal of Physical Chemistry C, 2021)
Carbon-based nanomaterials such as carbon nanotubes (CNTs) have a great potential for applications in the development of high performance thermoelectric (TE) materials because of their low-cost and for being environmentally friendly. Pristine nanotubes have, however, high electrical and thermal conductivities so that further nanoscale engineering is required to exploit them as TE materials. We investigate electron and phonon transport in CNT peapods to elucidate their potential advantage over pristine CNTs as basic TE elements. We show that the electron and phonon transport properties are sensitively modified by C60encapsulation, when the CNT-C60intermolecular interaction is strong enough to produce a periodic buckling of the CNT walls. Moreover, the phonon transmission is strongly suppressed at low and high frequencies, leading to a reduction of the phonon contribution to the overall thermal conductance. A similar effect has also been observed in the recently proposed phononic metamaterials. We obtain in general a larger TE figure of merit over a broad temperature range for the CNT peapod when compared with the pristine CNT, achieving an increase by a factor of 2.2 at 575 K. Our findings show an alternative route for the enhancement of the TE performance of CNT-based devices.
CRIS-Team Scopus Importer:2023-03-20